Exploring the non-pecuniary costs of the administrative burden of public procurement : a case of the Western Cape Department of Transport and Public Works - Adams, Azra Leoni (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPA)--Stellenbosch University, 2021.